Musical Analysis Structure and Violin Playing Technique in Suzuki Violin Book - Riyadi, Lanang; Yensharti, Yensharti (Virtuoso: Jurnal Pengkajian dan Penciptaan Musik, 2023)
This article aims to describe and provide an overview of the analysis of the musical structure and violin playing techniques contained in the works in Suzuki Violin Book Volume 1. The research contained in this article uses a qualitative method with a systematic content analysis approach, objectivity, and generalization. The works analyzed in this research are "Twinkle, Twinkle, Little Star", "Lightly Row", and "Song of the Wind". The results show that the three works are simple works that are appropriate as teaching materials for educators in teaching students who are just learning violin instruments. This is evidenced by violin playing that only uses the A string and E string with 1, 2, 3, and 0 (open string). The works are composed of intervals that make the melody movement dominated by stepping movements rather than jumping. In addition, the techniques that appear in these works are simple techniques such as up-bow, down-bow, tenuto, and staccato, and a little complicated for beginners is syncopation. So, the three works are the right works to learn for beginners.